(untitled) (International Journal of Engineering and Computer Science, 2017)
Nowadays the demand of network is increasing rapidly. The ever increasing usage of such network requirements additionally demands fast recovery from network failures. Multipath routing is one in all the most promising routing schemes to accommodate the various needs of the network. It has basic features like load balancing and improved bandwidth. Author Cho et al. introduced a reliable multipath routing scheme known as directed acyclic graphs. The property of directed acyclic graph is that they allow multipath routing with all possible edges whereas ensuring secured recovery from single point of failures. We have used the concept of DAG in our proposed method.